2018
DOI: 10.1136/neurintsurg-2018-014123
|View full text |Cite
|
Sign up to set email alerts
|

Downstream vascular changes after flow-diverting device deployment in a rabbit model

Abstract: BackgroundFlow diverters (FDs) are increasingly used in the treatment of intracranial aneurysms, and carry the risk of thromboembolic complications, even in patients treated with dual antiplatelet therapy. The effect of FDs on the downstream vascular is unknown. The aim of the study was to investigate vascular wall pulse wave velocity (PWV) and contractility changes following FD treatment in a rabbit model.MethodsFDs (Pipeline Embolic Device, Medtronic Inc., Irvine, California, USA) were implanted in the aorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…57 A recent study from our group demonstrated that elevated pulse wave velocity and vascular contractility in the distal aortic regions follow FD implantation in the rabbit model. 58 However, this study failed to show any cellular and structural changes in the distal segments. The ischemic hypothesis suggests that small thromboembolic infarcts, especially in the setting of dual antiplatelet therapy, subsequently undergo hemorrhagic transformation.…”
Section: Device Complications Delayed Intraparenchymal Hemorrhagecontrasting
confidence: 55%
“…57 A recent study from our group demonstrated that elevated pulse wave velocity and vascular contractility in the distal aortic regions follow FD implantation in the rabbit model. 58 However, this study failed to show any cellular and structural changes in the distal segments. The ischemic hypothesis suggests that small thromboembolic infarcts, especially in the setting of dual antiplatelet therapy, subsequently undergo hemorrhagic transformation.…”
Section: Device Complications Delayed Intraparenchymal Hemorrhagecontrasting
confidence: 55%
“…FD stents, redirecting blood flow from the aneurysm sac to parent vessel, have an immediate effect on distal hemodynamics. Alteration of FD stent on distal intracranial hemodynamics has been previously demonstrated in other measurements and in other models: observation of immediate increase in distal flow and wall shear stress, 5 and long-term increased vascular contractility in animal models 8 weeks after implant 15 have been reported. Even though it is intuitive that FD might affect the distal hemodynamic, there are only few objective in vivo measurements.…”
Section: Discussionsupporting
confidence: 53%
“…Significant increase in contractility and pulse wave velocity distal to FD in the aorta has also been reported. 5 It is possible that prolonged endothelial injury could be induced by implanted stents or ancillary devices during device implantation procedure. We demonstrated that FD implantation denude the endothelial layer in the parent artery.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that vascular contractility increased in the aorta of a rabbit model after FD-implantation as a potential mechanism of distal complications. 5 The cause of these distal vascular changes is still unknown, but several studies have suggested that the device itself may alter blood flow, causing changes in the vessel wall structure distal to the device. 6 Indeed, shear stress has been shown to increase vascular smooth muscle contractility, 7,8 and disrupted or turbulent blood flow can lead to changes in smooth muscle cell morphology causing abnormal vascular tone and vasospasms.…”
Section: Introductionmentioning
confidence: 99%